Reported progress under the student right-to-know act: how reliable is it? - Leslie Sundt Stratton; James N. Wetzel (Institute for the Study of Labor (IZA), 2006)
The Student Right-to-Know Act requires colleges to provide institution-specific information on graduation rates for students initially enrolling full-time in the fall term. Not all students, however, initially enroll full-time or in the fall term. We use longitudinal data on academic, degree-seeking students from the 1996/2001 Beginning Post-Secondary Survey to identify those students for whom statistics are and are not reported under the Act and to track their relative progress at two- and four-year institutions. We also examine the intra-institution correlation between reported and unreported students' progress to determine if the published statistics will at least allow relative comparisons. Our results indicate that the published progress rates are substantially higher than the progress rates for the unreported populations. Furthermore, while these rates are relatively comprehensive for and comparable across four-year institutions, they are neither for two-year institutions. Policy makers and prospective students will not make efficient decisions using such unreliable information.
urn:nbn:de:101:1-20080702321
Keywords: 330